Neutrophil-to-Lymphocyte Ratio as a Risk Factor for Mortality and Length of Stay in Neonatal Sepsis - Nandiyarizky, Desi; Ema Alasiry; A. Dwi Bahagia Febriani (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
The neutrophil-to-lymphocyte ratio (NLR) is inexpensive and included as part of complete blood counts studied in various clinical conditions and sepsis. Alterations in NLR have been associated with disease severity and outcomes. The study aimed to determine whether NRL can be a prognostic marker for mortality/length of stay in neonatal sepsis. This retrospective cohort study examined the relationship between high NLR and mortality/length of stay in neonatal sepsis in neonates treated at RSUP Dr Wahidin Sudirohusodo Makassar from January 2018 to December 2020. Data from 138 neonates with complete medical records were analyzed. The NLR value increased more with mortality outcomes and length of stay less than seven days. No significant association was found between NLR and patient outcomes or length of stay. The study has found no association between NLR and outcomes or length of hospital stay in neonatal sepsis.